Les rivalités entre les factions de pouvoir du régime franquiste, vues sous le prisme de la politique censoriale - Anne Laure Feuillastre (Amnis)
This paper would like to analyze how the Ministry of Information and Tourism became a battlefield for the two political families of the Caudillo’s government during second Francoism. Over the 1960s, reformists battled against technocrats linked to the Opus Dei within the government and fought for power. The censorial policy evolved according to the personality in charge of the Ministry: Manuel Fraga Iribarne, Minister between 1962 and 1969, tried to lead a political opening up but was confronted with the immobilist sector embodied by ecclesiastical authorities and technocrats. Using some concrete examples of official documents, plays and censorship archives, this work aims to highlight the infightings for power.